Micropropagation of Ornamental Plant Musa Beccarii through Tissue Culture Technique Using Suckers and Male Buds as Explants - Kamaludin, Rashid; Arash, Nezhadahmadi; Rofina Yasmin, Othman; Nurul Aina, Ismail; Shamrulazhar, Shamzir Kamal; Shahril, Efzueni (Elsevier Science, Ltd., 2012)
Musa beccarii is grouped under wild bananas and endemic in Borneo. This ornamental plant is among the most unique ornamental bananas that produce colorful and attractive flowers with small plant compared to the cultivated bananas for fruits. Micropropagation is a laboratory based tissue culture technique commonly used to propagate any plants. Micropropagation studies of these species have become important in order to increase the productivity for mass propagation in floriculture industry. This study was conducted to observe and determine the optimum sterilization procedure and media requirement for the regeneration of explants using in vitro method. Sterilization procedure for both suckers and male buds inflorescence for this ornamental banana were almost the same, whereas for suckers, 100% Clorox with tween 20 and 70% ethanol were used and for male buds, 70% ethanol was only used. It is found out that prolific multiple shoot formation and elongation were obtained from the suckers and male flower buds cultured on MS basal medium with 0.014mg/L BAP. Charcoal, coconut water, and gelrite (agar) were also added into the medium and PH was adjusted to 5.8. Unfortunately, the final phase was not able to perform as the plantlets were died after 5 weeks transplanting from media culture to the soil. It might be because of the sunlight that was too hot or the plant could not acclimatize to the new condition. So, the plantlets were not capable of supporting themselves in the soil.